Effect Of Various Types Of Liquid Organic Fertilizer On Growth And Yield Of Green Eggplant (Solanum melongena L) - Dian Triadiawarman (Universitas 17 Agustus 1945 Samarinda, 2019)
Effect Of Various Types Of Liquid Organic Fertilizer On Growth And Yield Of Green Eggplant (Solanum melongena L). Research on the effect of various types of liquid organic fertilizer on growth and yield of green eggplant (Solanum melongena L) was conducted on February up to May 2018 at Agrotechnology Experimental Farm, STIPER East Kutai.A single factor of completely randomized block design were used in this research, and analysis of variance were used for data analysis and for advance by a Duncan's test, on a significance level 5%. The treatment is giving various types of LOF (Liquid Organic Fertilizer) from goat manure, cow dung and chicken manure. Each type of LOF had six replication. Obtained data were analyzed by analysis of variance at a significance level 5%. The research results showed that application of various types of liquid organic fertilizer was non significant on plant height, number of leaves, flowering age and weight of eggplant.